Winning Women for Socialism: The Ontario CCF and Women, 1947-1961 - Azoulay, Dan (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1995)
This article examines the role of women in the Ontario Co-operative Commonwealth Federation (CCF) in the period 1947 to 1961. Taking a revisionist approach, it argues that the main concern of Ontario CCF women, as expressed through the Provincial Women's Committee, was with expanding the party's membership and support by attracting other women to the party, and not with advancing the equality of women, as the existing literature contends. It is further argued that women were not significantly under-represented in positions of power within the CCF, that the party's sexual division of labour was due largely to the timidity of its female members, and that the methods used to "win women for socialism" were practical and sensible under the circumstances.